Dampak Pandemi Covid-19 Terhadap Peningkatan Daya Beli Masyarakat Melalui Situs E-Commerce - Agus Wiastono; Wiwit Setyo Wardani (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
Currently, every individual must be prepared to face cultural shifts in which every demand must coexist with technology advancements. Most e-commerce enterprises may use this occasion to exhibit their market by buying and selling things online. E-commerce encompasses all development, marketing, sales, delivery, service, and consumer payment activities, with the assistance of a larger network of business partners. The COVID-19 epidemic is presently affecting the world, and the government is seeking to limit its spread by adopting social distancing measures to restrict direct public engagement. purchases made through e-commerce in response to requests